Mauritania : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This paper reviews economic developments in Mauritania during 1996-99. Mauritania continued its ambitious program of economic reforms in 1995-97. The government exercised firm control over public expenditures and ran a fiscal surplus in both 1996 and 1997. The decline in broad money in 1995-96 was reversed in 1997, reflecting increased confidence in ouguiya-denominated assets, in part owing to the implementation of financial market reforms. These policies and reforms resulted in sustained GDP growth, which averaged 4.6 percent annually over 1995-97, that is, 1.8 percent in real per capita income growth.